The impact of promotional mix towards customer-based brand equity on Faiza in Johor / Mohd Fitri Mohd Aznam - Mohd Aznam, Mohd Fitri (Faculty of Business and Management, 2010)
Brand equity is intangible due to it is feelings, images and thoughts that consumers associate with a product. Companies will not have so much time to build brand equity and in the future as they will have to pursue it. The reasons are conditions, things and people changing quickly. To maintain the current position, the company must determine what types of promotional mix might influence the consumer-based brand equity in the market. The objectives for this research are: to identify the level of customer-based brand equity of Faiza brand, to determine whether the promotional mix is having significant relationship with customer-based brand equity of Faiza, to identify which promotional mix influence the customer-based brand equity the most and to give the recommendation and suggestion about the best promotional mix that can be used by Faiza Marketing Sdn. Bhd. The exploratory research, descriptive research and causal research are use in order to collect the data. The sampling frame is 40 respondents each are selected from areas covered by three salesman of Faiza Marketing and the sampling size is 123 respondents who have experienced with Faiza promotional activities and reside within the area of Johor. This research was conducted by using stratified sampling. The populations are divided into homogeneous subgroups and then a simple random sample is taking from each subgroup. In this research, primary data was use to get the data and findings. Personal interview and questionnaire developments used as the sources for primary data in getting more information related to the study. The finding was the respondents are agreeing with all statements toward customer-based brand equity. The promotional mix does not have significant relationship with customer-based brand equity. Lastly, sales promotion and sponsorship are the most influencing tools toward the customer-based brand equity but the most significant relationship is sales promotion.